2009
DOI: 10.22358/jafs/66389/2009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oocyte quality and semen donor on the efficiency of <i>in vitro</i> embryo production in cattle

Abstract: The aim of the study was to determine whether immature bovine oocytes selected by morphology and BCB test (brilliant cresyl blue) and used for in vitro embryo production would increase the blastocyst rate when inseminated with sperm derived from bulls of reduced in vitro fertilizability.To relate oocyte quality and bull effect to blastocyst quality, morphology, ability for hatching and caspase-3 activity (marker of apoptosis) were evaluated.Both, oocytes originating from BCB+ and from Control COCs exhibited hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
1
5
1
Order By: Relevance
“…oocytes compared with unstained oocytes [ 24 , 31 , 32 , 34 , 35 , 39 , 41 , 46 ]. However, in the present work and other studies [ 36 , 37 , 38 , 44 , 48 ] no significant differences between unstained oocytes and BCB-pos. oocytes were noticed.…”
Section: Discussioncontrasting
confidence: 76%
“…oocytes compared with unstained oocytes [ 24 , 31 , 32 , 34 , 35 , 39 , 41 , 46 ]. However, in the present work and other studies [ 36 , 37 , 38 , 44 , 48 ] no significant differences between unstained oocytes and BCB-pos. oocytes were noticed.…”
Section: Discussioncontrasting
confidence: 76%
“…We observed that after re-placing in culture the cells maintained their phenotype although part of them did not attach which is a normal observation as around 1/5 of the frozen cells dies during the freezing/thawing procedure [ 43 ]. This method of freezing has been routinely performed in our laboratory to freeze somatic cells [ 44 , 45 ] and mesenchymal stem cells [ 46 ] used as donors of nuclei for somatic cell cloning purposes as well as VERO cells used as co-culture cells for bovine and goat embryo in vitro culture [ 47 , 48 ]. Presently the cooling protocol of MSCs from various tissues and species is mostly based on controlled freezing [ 49 ] although different approaches of cryopreservation of porcine MSC are rather scarcely described compared to other species.…”
Section: Discussionmentioning
confidence: 99%
“…IVF was performed according to our standard protocol that was previously described [ 20 , 21 ]. Briefly, after 22–24 hrs of maturation, the selected oocytes were fertilised using frozen semen from single bull.…”
Section: Methodsmentioning
confidence: 99%
“…After washing and partial deprivation of the expanded cumulus, the mature COCs were transferred in groups of 10 into 50 μ L of fertilisation medium. Gametes were incubated together for 18 to 21 h at 38.5°C under 5% CO 2 in air [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation